Sodium lasalocid in blackbelly sheep feed (Ovis aries) - Aliaga Gutiérrez, Jorge L. (2020)
The objective was to evaluate the effect of sodium lasalocid supplementation in the productive characteristics and economics in Blackbelly sheep in growth. It was used 11 male of 5 months old, randomly distributed in two groups that fed with agro-industrial residues that was added sodium alkaloid (LS) in one treatment. It was used two treatments T1 (without LS) and T2 (whit 60mg LS / kg). Feed intake (kg), weight gain (kg), height gain (cm) and carcass yield (%) was evaluated in each animal. It was used the multivariate analysis of variance of a completely randomized design with covariance for the variables feed consumption, weight gain, feed conversion and height increase. To evaluate of carcass yield it was used a completely randomized design with covariance. The results obtained in each treatment (T1 vs. T2) were: food consumption (63,85 vs. 63,97), weight gain (12,91 vs. 13,33), feed conversion (4,94 vs. 4,80), size increase (10,19 vs. 10,09) and carcass performance (48,60 vs. 46,66). There are not statistical differences between treatments (p > 0,05), in the variables studied. As a result of this study it is possible to conclude that the addition the 60 mg of lasalocid sodium per kg in feed rations for Blackbelly sheep did not improve the performance.